The impact of using different costing methods on the results of an economic evaluation of cardiac care: microcosting vs gross-costing approaches - Clement (Nee Shrive), Fiona M.; Ghali, William A.; Donaldson, Cam; Manns, Braden J. (Health economics, 2009)
Background: Published guidelines on the conduct of economic evaluations provide little guidance regarding the use and potential bias of the different costing methods. Objectives: Using microcosting and two gross‐costing methods, we (1) compared the cost estimates within and across subjects, and (2) determined the impact on the results of an economic evaluation. Methods: Microcosting estimates were obtained from the local health region and gross‐costing estimates were obtained from two government bodies (one provincial and one national). Total inpatient costs were described for each method. Using an economic evaluation of sirolimus‐eluting stents, we compared the incremental cost–utility ratios that resulted from applying each method. Results: Microcosting, Case‐Mix‐Grouper (CMG) gross‐costing, and Refined‐Diagnosis‐Related grouper (rDRG) gross‐costing resulted in 4‐year mean cost estimates of $16 684, $16 232, and $10 474, respectively. Using Monte Carlo simulation, the cost per QALY gained was $41 764 (95% CI: $41 182–$42 346), $42 538 (95% CI: $42 167–$42 907), and $36 566 (95% CI: $36 172–$36 960) for microcosting, rDRG‐derived and CMG‐derived estimates, respectively (P<0.001). Conclusions: Within subject, the three costing methods produced markedly different cost estimates. The difference in cost–utility values produced by each method is modest but of a magnitude that could influence a decision to fund a new intervention. Copyright © 2008 John Wiley & Sons, Ltd.